KAJIAN HUKUM ATAS PERBUATAN MELAWAN HUKUM TERHADAP PENGUASAAN HAK MILIK TANAH PADA SERTIFIKAT GANDA - Sri Putri Mada Siltia Ughude; I Made Sarjana (Fakultas Hukum Unversitas Udayana, 2025)
Permasalahan sertifikat ganda atas tanah menimbulkan ketidakpastian hukum serta berpotensi mengakibatkan perbuatan melawan hukum (PMH) yang merugikan pemegang hak milik yang sah. Penelitian ini bertujuan untuk mengkaji pengaturan hak milik atas tanah menurut Undang-Undang Nomor 5 Tahun 1960, bentuk dan unsur PMH dalam penguasaan tanah dengan sertifikat ganda, tanggung jawab hukum Badan Pertanahan Nasional (BPN), serta akibat hukum dari penerbitan sertifikat ganda tersebut. Metode yang digunakan adalah penelitian hukum yuridis normatif, dengan pendekatan perundang-undangan dan konseptual. Hasil penelitian menunjukkan bahwa hak milik atas tanah merupakan hak terkuat dan terpenuh yang dijamin oleh UUPA, sementara penerbitan sertifikat ganda dapat dikategorikan sebagai perbuatan melawan hukum apabila dilakukan dengan cara yang bertentangan dengan hukum atau menimbulkan kerugian bagi pihak lain. BPN sebagai lembaga pelaksana pendaftaran tanah memiliki tanggung jawab hukum, baik secara administratif maupun perdata, apabila terbukti lalai dalam menerbitkan sertifikat ganda. The issue of duplicate land certificates (double certificates) has created legal uncertainty and often constitutes an unlawful act (perbuatan melawan hukum) that harms the legitimate landowner. This research aims to examine the legal regulation of land ownership rights under Law Number 5 of 1960 on Basic Agrarian Principles (UUPA), to analyze the forms and elements of unlawful acts in the possession of land with double certificates, to assess the legal responsibility of the National Land Agency (Badan Pertanahan Nasional/BPN), and to identify the legal consequences of issuing duplicate land certificates. This study applies a normative juridical research method, employing statutory and conceptual approaches. The findings reveal that land ownership rights under the UUPA represent the strongest and most complete rights that can be held by individuals, yet they are bound by the social function of land and the principle of legal certainty. The existence of double certificates may be classified as an unlawful act when there is intentional misconduct, negligence, or abuse of authority causing harm to other parties. The BPN bears both administrative and civil liability for its officials’ negligence in the land registration process, which may result in the issuance of invalid certificates. The legal consequences of issuing double certificates include the administrative cancellation of invalid certificates, loss of legal certainty for the rightful owner, and potential civil lawsuits against the BPN. Strengthening supervision, data transparency, and digital registration systems are essential to uphold legal certainty, accountability, and justice in Indonesia’s land administration system.